Implant and Prosthodontic Survival Rates with Implant Fixed Complete Dental Prostheses in the Edentulous Mandible after at Least 5 Years: A Systematic Review. (11th January 2013) - Papaspyridakos, Panos; Mokti, Muizzaddin; Chen, Chun‐Jung; Benic, Goran I.; Gallucci, German O.; Chronopoulos, Vasilios
Abstract Background The treatment of mandibular edentulism with implant fixed complete dental prostheses (IFCDPs) is a routinely used treatment option. Purpose The study aims to report the implant and prosthodontic survival rates associated with IFCDPs for the edentulous mandible after an observation period of a minimum 5 years. Materials and Methods An electronic MEDLINE/PubMED search was conducted to identify randomized controlled clinical trials and prospective studies with IFCDPs for the edentulous mandible. Clinical studies with at least 5‐year follow‐up were selected. Pooled data were statistically analyzed and cumulative implant‐ and prosthesis survival rates were calculated by meta‐analysis, regression, and chi‐square statistics. Implant‐related and prosthesis‐related factors were identified and their impact on survival rates was assessed. Results Seventeen prospective studies, including 501 patients and 2, 827 implants, were selected for meta‐analysis. The majority of the implants (88.5% of all placed implants) had been placed in the interforaminal area. Cumulative implant survival rates for rough surface ranged from 98.42% (95% confidence interval [CI]: 97.98–98.86) (5 years) to 96.86% (95% CI: 96.00–97.73) (10 years); smooth surface implant survival rates ranged from 98.93% (95% CI: 98.38–99.49) (5 years) to 97.88% (95% CI: 96.78–98.98) (10 years). The prosthodontic survival rates for 1‐piece IFCDPs ranged from 98.61% (95% CI: 97.80–99.43) (5 years) to 97.25% (95% CI: 95.66–98.86) (10 years). Conclusion Treatment with mandibular IFCDPs yields high implant and prosthodontic survival rates (more than 96% after 10 years). Rough surface implants exhibited cumulative survival rates similar to the smooth surface ones (p > .05) in the edentulous mandible. The number of supporting implants and the antero‐posterior implant distribution had no influence (p > .05) on the implant survival rate. The prosthetic design and veneering material, the retention type, and the loading protocol (delayed, early, and immediate) had no influence (p > .05) on the prosthodontic survival rates.